2010
DOI: 10.1007/s00299-010-0876-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression patterns of two Arabidopsis phytocystatin genes, AtCYS1 and AtCYS2, during development and abiotic stresses

Abstract: The phytocystatins of plants are members of the cystatin superfamily of proteins, which are potent inhibitors of cysteine proteases. The Arabidopsis genome encodes seven phytocystatin isoforms (AtCYSs) in two distantly related AtCYS gene clusters. We selected AtCYS1 and AtCYS2 as representatives for each cluster and then generated transgenic plants expressing the GUS reporter gene under the control of each gene promoter. These plants were used to examine AtCYS expression at various stages of plant development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 58 publications
0
40
0
1
Order By: Relevance
“…Although cystatin family genes have been identified in some plant species, only a few cystatins in plants have been well characterized, which show their function in programmed cell death (Solomon et al 1999;Zhao et al 2013), seed germination (Hwang et al 2009), plant defense against pathogens (Belenghi et al 2003;Gutierrez-Campos et al 1999), response to insect attack (Goulet et al 2008;Konrad et al 2008) and abiotic environmental stresses (Hwang et al 2010). These works reveal that plant cystatins are crucial to several essential processes in plant development as described above, especially in the process of sexual plant reproduction and abiotic/biotic stresses, suggesting that cystatins are critical not only for plant vegetative growth, but also for plant fertility and seed formation.…”
Section: Introductionmentioning
confidence: 99%
“…Although cystatin family genes have been identified in some plant species, only a few cystatins in plants have been well characterized, which show their function in programmed cell death (Solomon et al 1999;Zhao et al 2013), seed germination (Hwang et al 2009), plant defense against pathogens (Belenghi et al 2003;Gutierrez-Campos et al 1999), response to insect attack (Goulet et al 2008;Konrad et al 2008) and abiotic environmental stresses (Hwang et al 2010). These works reveal that plant cystatins are crucial to several essential processes in plant development as described above, especially in the process of sexual plant reproduction and abiotic/biotic stresses, suggesting that cystatins are critical not only for plant vegetative growth, but also for plant fertility and seed formation.…”
Section: Introductionmentioning
confidence: 99%
“…These genes and proteins are designed to protect cells from damage. The PhyCys are thought to help regulate endogenous processes and guard against the effects of various biotic or abiotic stresses (Gutierrez-Campos et al 1999;Arai et al 2002;Haq et al 2004;Valdés-Rodríguez et al 2007;Zhang et al 2008;Hwang et al 2010). We previously identified cystatin genes within the entire apple genome and monitored their transcription patterns in several tissues and in response to drought, low temperature, heat, ABA, and oxidative stress (Tan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PhyCys is also considered important for the acquisition of abiotic stress tolerance (van der Vyver et al 2003;Zhang et al 2008;Benchabane et al 2010;Hwang et al 2010;Wang et al 2012;Sun et al 2014). For example, transformed tobacco plants expressing the rice cystatin OC-I are more resistant to the negative impacts of chilling stress on photosynthesis (van der Vyver et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Gutiérrez-Campos et al (2001) suggested a mechanism for cysteine protease regulation by cystatins at the cytoplasmic level, leading to variations in the cellular differentiation and elongation processes. A previous study showed that cystatins are induced by harm (Hwang et al, 2010); thus, during the foliar infiltration process of MpNEP2, there may have been increased local expression of endogenous cystatins and reduced protein activity that induces necrosis. Previous studies showed that overexpression of AtCys1 inhibited PCD caused by increased hydrogen peroxide, among other factors (Belenghi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%